Honey, Tradition and Sustainability: Opportunities for the Development of Tamara Bakale’s Family Farm - Mahnić, Nikola; Goričar, Anja; Petrič, Carina; Vinčić, Lorena (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
Tamara Bakale’s family farm is located in the municipality of Topusko, where she has been engaged in beekeeping for 26 years. The farm offers a variety of products, including honey, propolis and bee venom, the latter of which is used in the pharmaceutical industry for its medicinal properties. Beekeeping in this region has a long tradition, and Topusko stands out as an important region for beekeeping in Croatia. The aim of the research was to analyse the current business practices of the farm and develop a strategy for further growth, including the introduction of online shopping and the development of a tourist experience. The research included a SWOT analysis that identified farm's strengths, weaknesses, opportunities and threats. The main opportunities include the collection of bee venom and apitherapy, while the threats are climate change and competition in the market. The proposed strategy includes the creation of an online shop that would allow wider availability of the products and the promotion of the farm's story to increase visibility and sales on the national and international market, as well as the creation of a tourist experience based on the establishment of apitherapy and a museum.